Foreign bodies in the airways in children - Toman, Piotr (Journal of Education, Health and Sport, 2019)
Foreign bodies in the airways in children are a very important diagnostic and therapeutic problem. With these cases meet both emergency rooms, emergency departments, general pediatric wars and ENT wards. Aspiration of a foreign body is a frequent factor causing respiratory diseases along with its inefficiency and one of the more frequent causes of sudden deaths in children up to 6 years of age. In the majority of retrospective studies, aspiration of foreign bodies concerns children aged 1-3 years, with a male predominance. The main clinical symptoms accompanying the presence of a foreign body in the airways are cough, dyspnoea, vomiting. IIn each case, diagnostic imaging should be carried out. The basic test is a chest X-ray. In cases of prolonged inflammation of the respiratory tract in children, despite the negative history and no changes in chest radiological examination, the aspiration of the foreign body should be considered. In any case of suspicion of a foreign body, an absolute indication is bronchoscopy.